Food availability alters community co‑occurrence patterns at fine spatiotemporal scales in a tropical masting system - Peter Jefrey Williams; Anna K. Moeller; Alys Granados4 ·; Henry Bernard; Robert C. Ong; Jedediah F. Brodie (Springer-Verlag, 2022)
Patterns of co-occurrence among species can help reveal the structure and assembly of ecological communities. However, studies have been limited by measuring co-occurrence in either space or time but not both simultaneously. This is especially problematic in systems such as masting forests where resources are highly variable, meaning that spatial use and co-occurrence patterns can change on fne spatiotemporal scales. We develop an analytical framework for assessing species co-occurrence at fne spatial and temporal scales simultaneously and apply these models to a camera trapping dataset from Borneo. We sought to determine how substantial variation in food availability across space and time afects co-occurrence among terrestrial vertebrates. We detect many signifcant, mostly positive, co-occurrence patterns among species, but almost entirely in unlogged forest and during dipterocarp mast years. The most strongly co-occurring pair of species, bearded pig (Sus barbatus) and sambar (Rusa unicolor), only positively co-occur in areas and years when fruit is locally abundant. Species occurrences in logged forest and non-mast years are mostly random with respect to other species. This suggests that frugivore–granivore species positively co-occur when resources are plentiful (i.e., large trees are present and fruiting), likely because they use the same resources; these patterns disappear when food availability is lower. Our approach demonstrates the utility of measuring co-occurrence in space and time together and highlights the importance of resource abundance for driving the co-occurrence structure of communities. Furthermore, our method could be broadly applied to other systems to assess fne-scale spatiotemporal patterns across a range of taxa.